Chinese Immersion Teachers in the U.S.: Perceptions and Needs in Their Teacher Preparation Programs - Mengyao Chen; Jiahang Li; Yongling Zhang Gorke (MDPI AG, 2024)
Language immersion has been an emerging educational method for K-12 students to acquire foreign languages. Despite its effectiveness, there are limited teacher education programs designed specifically for language immersion educators. Thus, many language immersion teachers have been applying knowledge learned from general teacher educational programs, which are not designed for language immersion settings, in their daily teaching. Simultaneously, language immersion programs, especially Chinese immersion programs, have identified multiple educational challenges related to curriculum design and content teaching, classroom management, and cross-cultural communications. This study aims to address these challenges from the perceptions of six selected Chinese immersion teachers towards their teacher preparation programs via qualitative in-depth case studies. The participant selection considers various education and teaching backgrounds of Chinese immersion teachers to represent a wide range of perspectives. The results show that the educational philosophy and psychology theories and practices, curriculum and instruction, cross-cultural competence, and practicum in existing preparation programs contribute positively towards immersion teaching in the U.S. However, Chinese immersion teachers demand more social-emotional learning and diversity, equity, and inclusion preparation. Potential solutions to these challenges require synergistic efforts from the current teacher preparation programs, Chinese immersion programs, and policymakers.